Association between physical activity trajectories and successful aging in middle-aged and elderly Chinese individuals: a longitudinal study - Xing Zhang; Xiyan Niu; Mengdi Wang; Qiannan Li; Huiling Feng; Yanli Wang; Jinghua Ma (BMC Public Health)
Abstract Background Physical activity (PA) varies among middle-aged and older individuals, and insufficient or excessive in activity are associated with an individual’s health status. However, the associations between the trajectory of physical activity and the health status of middle-aged and older adults have been little studied. The study aims to explore the association between PA trajectories and successful aging in middle-aged and older adults. Methods This study used data from the CHARLS in 2013 to 2020. Physical activity was measured with the IPAQ Short Form and total weekly energy expenditure was calculated for different intensities of exercise. The assessment of successful aging includes the following five aspects: the absence of major diseases, no physical impairment, high cognitive function, no depression, and active participation in social activities. Group-based trajectory modeling (GBTM) was used to identify PA trajectories and logistic regression was performed to explore the association between the trajectories of PA and the incidence of successful aging. Results A total of 1,413 individuals participated in the follow-up study. Three PA trajectories were identified based on GBTM model: stable low, decreasing and increasing. The increasing trajectory (17.1%) had a higher prevalence of successful aging than the stable low trajectory (14.0%) and the decreasing trajectory (15.7%). The sensitivity analyses were generally consistent with the main results. Conclusion Our study identified three PA trajectories and found that increasing PA trajectory has a higher prevalence of successful aging compared with stable low and decreasing trajectories among Chinese middle-aged and older adults. The findings underscore the importance of monitoring changes in physical activity in middle-aged and older individuals, which provides new ideas for achieving successful aging.